(3Jbdjd GdYeGdIs - (3CMeO(B, (3eGgQs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2000)
(3eGgjI hCgejI JNajV GdYeGdI(B- (3eTGcd JNajV GdYeGdI (B- (3GdEYOGO dYedjI JNajV GdYeGdI(B- (3GSJQGJjLjGJ heOGNd JNajV GdYeGdI(B- (3OQGSI GdLhGfH GdbGfhfjI dJNajV GdYeGdI(B- (3JCKjQ JNajV GdYeGdI Ydi Gdgjcd GdJfXjej (B- (3JMdjd gjcd hMQcI GdYeGdI HGdefXeI(B- (3CSGdjH JNajV GdYeGdI(B- (3eYGjjQ JNajV GdYeGdI(B- (3JMOjO YOO hfhY GdYeGdI GdJj SjJe GdESJZfGA YfgG(B- (3GdYdGbI Hjf JNajV GdYeGdI hGdHWGdI(B- (3JLGQH GdOhd aj JNajV GdYeGdIs
Keywords: (3GdJTZjds; (3GdYeGdIs